МЕКА МОЋ И НАДМЕТАЊЕ ВЕЛИКИХ СИЛА - Šekara, Vladana (POLITEIA, 2025)
Joseph Nye, Soft Power and Great-Power Competition – Shifting Sands in the Balance of Power Between the United States and China, Springer, 2023.